2008
DOI: 10.1007/s00280-008-0746-2
|View full text |Cite
|
Sign up to set email alerts
|

A phase II study of pegylated-camptothecin (pegamotecan) in the treatment of locally advanced and metastatic gastric and gastro-oesophageal junction adenocarcinoma

Abstract: Pegamotecan has activity in this patient population and was generally well-tolerated. The favourable rate of haematological toxicities and diarrhoea compared with irinotecan in similar studies suggests that pegamotecan could be combined with other active agents in further studies in this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(29 citation statements)
references
References 27 publications
0
28
0
1
Order By: Relevance
“…They are based on the traditional cytotoxic drugs (e.g. platinates [145,146], doxorubicin [147,148], camptothecin and analogues [149][150][151][152][153][154][155][156][157][158][159], paclitaxel/docetaxel [160][161][162][163][164], methotrexate [165], and irinotecan [166,167]). Xyotax (CT-2103 or OPAXIO), a PGA-paclitaxel conjugate, and NKTR-102, a polymer conjugate of irinotecan, are both currently in phase III clinical trials, being the conjugates closest to approval and market availability [164,[166][167][168].…”
Section: Polymer Therapeuticsmentioning
confidence: 99%
“…They are based on the traditional cytotoxic drugs (e.g. platinates [145,146], doxorubicin [147,148], camptothecin and analogues [149][150][151][152][153][154][155][156][157][158][159], paclitaxel/docetaxel [160][161][162][163][164], methotrexate [165], and irinotecan [166,167]). Xyotax (CT-2103 or OPAXIO), a PGA-paclitaxel conjugate, and NKTR-102, a polymer conjugate of irinotecan, are both currently in phase III clinical trials, being the conjugates closest to approval and market availability [164,[166][167][168].…”
Section: Polymer Therapeuticsmentioning
confidence: 99%
“…Results from clinical trials showed that the conjugate was highly tolerated with significantly reduced toxicity as compared to the commercial formulation. However, quick hydrolysis in vivo of the linkage caused a parallel toxicity to that of the native drug, leading to the failure of drug development of this conjugate [49,50]. In short, the in vivo metabolism of small-molecule drugs can be manipulated through PEGylation, for example, utilizing a suitable linkage and controlling the release speed of parent drugs.…”
Section: Metabolism Of Pegylated Small-molecule Drugsmentioning
confidence: 99%
“…PEG conjugation enhances the solubility, bioavailability, and anti-tumor activity of various anticancer drugs, including camptothecin and curcumin. 16,17) Owing to the hydrophilic nature of PEG, the prepared PEG-CK conjugate (0.7 mg) was readily soluble in 450 μL of water, whereas, due to the hydrophobic nature of free CK, it was insoluble even at much lower concentrations (Fig. 1(D)).…”
mentioning
confidence: 99%